2015
DOI: 10.1080/00140139.2015.1046498
|View full text |Cite
|
Sign up to set email alerts
|

Need for recovery among male technical distal on-call workers

Abstract: The objectives of this study were to (1) examine whether need for recovery differs between workers (i) not on-call, (ii) on-call but not called and (iii) on-call and called, and (2) investigate the associations between age, health, work and social characteristics with need for recovery for the three scenarios (i-iii). Cross-sectional data of N = 169 Dutch distal on-call workers were analysed with multivariate logistic regression. Need for recovery differed significantly between the three scenarios (i-iii), wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…A sample of shift workers with regular shifts, unregularly shifts, on call workers, and workers on day shifts. Data was collected within the sampling frame of the ‘Shift Your Work’ study; a study about the effects of irregular night and shift work on health, work role functioning and social life [ 26 , 27 ]. Regarding health status this is a heterogeneous sample.…”
Section: Methodsmentioning
confidence: 99%
“…A sample of shift workers with regular shifts, unregularly shifts, on call workers, and workers on day shifts. Data was collected within the sampling frame of the ‘Shift Your Work’ study; a study about the effects of irregular night and shift work on health, work role functioning and social life [ 26 , 27 ]. Regarding health status this is a heterogeneous sample.…”
Section: Methodsmentioning
confidence: 99%
“…For certain types of work, these interventions may be particularly helpful (e.g. telework carried out in one's home, on-call work; van de Ven et al, 2015;Ziebertz et al, 2015). This field of research may also benefit from the emerging line of research on people's role in actively shaping their recovery process, switching roles and satisfying psychological needs (e.g.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…While there are a number of benefits to on-call working arrangements, there are number of potentially adverse consequences for workers [5][6][7][8]. Previous research has shown that when on-call at night, workers' sleep is often disturbed by the call to attend work [4,9], and may be disturbed even in the absence of receiving a call such that simply being on-call can be detrimental to sleep [10][11][12][13]. Of concern, a recent study reported that 80% of Australian on-call workers obtained less than the recommended 7 h of sleep during on-call periods, at an estimated public health cost of $137 million (AUD) [14].…”
Section: Introductionmentioning
confidence: 99%